Efektifitas Diplomasi Digital dalam Promosi Wisata Halal Indonesia untuk Mencapai Nation Branding - Fenti Agustina, Rifqi Ananta Haidar, Fendi Irawan, Abdul Azis, Rika Isnarti (UIR Press, 2021)
Indonesia is still lacking in maximizing the use of digital technology to promote Indonesian halal tourism. In fact, Indonesia's digital technology is able to create and encourage Indonesia's nation branding as a world halal tourist destination. This study explains how the effectiveness of Indonesia's digital diplomacy in Indonesia's halal tourism promotion strategy. The method used in this research is qualitative method. The qualitative method was chosen by the author because the author wants to understand and interpret the dynamics of the use of social media, especially in the promotion of Indonesian halal tourism. Through the use of this method, the author will find out how effective digital diplomacy is in promoting Indonesian halal tourism to improve its nation branding. The data collection methods used are social media-based research and document-based research. This paper finds that each social media has different capabilities in promoting Indonesian halal tourism. Morover, the authors found four effective strategies in promoting Indonesian halaltourism through digital diplomacy. Nation Branding Indonesia as a halal tourist destination is quite good. This is evidenced by the presence of international actors who have recognized Indonesian halal tourism such as international institutions, international companies, and individuals.